2022
DOI: 10.1371/journal.pone.0271598
|View full text |Cite
|
Sign up to set email alerts
|

Astragalus polysaccharides and astragaloside IV alleviate inflammation in bovine mammary epithelial cells by regulating Wnt/β-catenin signaling pathway

Abstract: The Wnt/β-catenin signaling regulates cell renewal and repair and is closely associated with inflammation. Astragalus polysaccharides (APS) and astragaloside IV (AS-IV), which are the main active substances extracted from Radix Astragali, protect cells by regulating Wnt signaling in cells, exerting antiinflammatory, antioxidant, and antistress effects. However, the mechanisms by which APS and AS-IV interact with Wnt signaling to achieve their therapeutic effects in bovine mammary epithelial cells (BMECs) are n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Previous studies have shown that AS-IV has an anti-inflammatory effect and is negatively correlated with inflammatory factors, such as TNF-α, IL-6 and IL-1β 24,25 . In this study, we used a cytometric bead array method to assess the effect of AS-IV on inflammatory cytokines in response to D-GalN/LPS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that AS-IV has an anti-inflammatory effect and is negatively correlated with inflammatory factors, such as TNF-α, IL-6 and IL-1β 24,25 . In this study, we used a cytometric bead array method to assess the effect of AS-IV on inflammatory cytokines in response to D-GalN/LPS.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that AS-IV has an anti-inflammatory effect and is negatively correlated with inflammatory factors, such as TNF-α, IL-6 and IL-1β. 24,25 In this study, we used a cytometric bead array method to assess the effect of AS-IV on inflammatory cytokines in response to D-GalN/LPS. The results showed that monocyte chemoattractant protein-1 (MCP-1) was significantly decreased, while IL-10, IL-6, IFN-β, granulocyte-macrophage colony-stimulating factor (GM-CSF), IL-12p70, IL-1β and IL-23 ( P < 0.05) were significantly increased in the AS-IV group compared to the D-GalN/LPS group (all P < 0.05) (Figure 3).…”
Section: As-iv Reduces Inflammatory Cytokines In Response To D-galn/lpsmentioning
confidence: 99%
“…[29] Huangqi reduced oxidative stress by restraining ROS production, [30] improving mitochondrial dysfunction, [31] and enhancing Nrf2 activation and HO-1 and NQO1 expression. [32] Inflammation: Huangqi mediated multiple signaling pathways to exert anti-inflammatory effects, such as mediating the TLR-4/ NF-kb p65 pathway [33] and regulating the Wnt/β-catenin signaling pathway, [34] down-regulating the expression of inflammatory factors IL-1, IL-6, and TNF-α, and inhibiting the JNK signaling pathway associated with oxidative stress, reducing the expression of transcriptional level of the puc gene. [35] These 3 pathological processes may be the main pharmacological mechanism of Huangqi, which was also the focus of the research area of Huangqi.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also found that AS-IV and APS can decrease the expression of inflammatory factors, such as IL-6, IL-8, and TNF-α, oxidative factors like ROS and MDA, and the apoptotic factor caspase-3 in inflammatory cells. Furthermore, the expression of β-catenin is activated in inflammatory cells for cytoprotection (Fan, 2021). AR treatment (2.1 g/kg for 12 weeks) in STZ-induced DN rats can reduce 24-hour urine protein quantification, attenuate interstitial pathological damage, and inhibit the expression of wnt4, β-catenin, and TGF-β1 in the renal interstitium, thus playing a role in kidney protection and slowing down the process of interstitial fibrosis in DN rats (Deng and Fang, 2012).…”
Section: Wnt/β-catenin Signaling Pathwaysmentioning
confidence: 99%